A Bio-Crypto Protocol for Password Protection Using ECC - Srinivasan Nagaraj; G.V.S.P. Raju; G Apparao; B. Kishore (Institute of Advanced Engineering and Science, 2015)
In information security the following security parameters like, integrity , non repudiation and confidentiality , authentication must be satisfied. To avoid thievery of organization resources it needs be secured in more efficient way and there is always demand for different levels of security attacks include virus , brute force and Eveadroper in business that organizations make use of voice biometrics an attractive low-cost. Voice biometrics is the cheapest among the other biometrics and used all levels for management to buy readily available metric and it is the way of identifying individuals remotely with high level of accuracy . In this work, we have been designed a new password- authentication approach that provides security using voice biometrics for authentication and uses the device itself into an authenticator which uses voice itself as its passwords and we are primarily interested in keys that can be temporally reproduced on the same device from the same user’s voice. Public and private keys are generated randomly from the user's voice and stored in the voice file(.wav).This Method uses voice recognition , include the operation of register( recording feature ) or voice prints and storing of one or more voice passwords into the database. It uses ECDSA to perform the authentication process that matching the voice sample with the database. The recognition, entity makes the database to decide that the sample is matched to perform an operation or not. Our proposed approach generates cryptographic keys from voice input itself and this algorithm developed an adhoc basis. It can effectively defend attacks specially brute force attack in system networks.